Prevention of Vascular Dysfunction after Preeclampsia: A Potential Long-Term Outcome Measure and an Emerging Goal for Treatment. (8th December 2011) - Lazdam, Merzaka; Davis, Esther F.; Lewandowski, Adam J.; Worton, Stephanie A.; Kenworthy, Yvonne; Kelly, Brenda; Leeson, Paul
Abstract : Preeclampsia is increasingly being recognised as more than an isolated disease of pregnancy. In particular, preeclampsia has emerged as an independent risk factor for maternal cardiovascular disease and has recently been recognised as a risk factor for cardiovascular disease in children exposed in utero. Preeclampsia and cardiovascular disease may share important pathophysiological and molecular mechanisms and further investigation into these is likely to offer insight into the origins of both conditions. This paper considers the links between cardiovascular disease and preeclampsia and the implication of these findings for refinement of the management of patients whose care is complicated by preeclampsia.